การระบุและการประกอบหน่วยการสร้างในขั้นตอนวิธีประมาณการแจกแจง - เฉลิมทรัพย์ สังขวิจิตร (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
To propose a novel way to look at Building Blocks (BB) called "Fragments". Fragments have simple and explicit structures. They can be used to study the working mechanism of Genetic Algorithms (GAs) to understand how Building Blocks actually work. The process of GA is divided into two parts: BB identification and BB composition from the point of view of knowledge sharing. Based on this concept, seven new algorithms are proposed to show different ways to manipulate Fragments. The proposed algorithms are tested with seventeen benchmark problems and the results show that Fragments can help to understand Genetic Algorithms in the perspective of Building Blocks processing. The algorithms based on Fragments can be applied in practice and this knowledge leads to development of better algorithms.